Interactions of Pseudomonas aeruginosa with Acanthamoeba polyphaga Observed by Imaging Flow Cytometry. Issue 5 (15th April 2019) - Dey, Rafik; Rieger, Aja M.; Stephens, Caroline; Ashbolt, Nicholas J.
Abstract: Pseudomonas aeruginosa is a Gram‐negative bacterium that is abundant in the environment and water systems, with strains that cause serious infections, especially in patients with compromised immune systems. In times of stress or as part of its natural life cycle, P. aeruginosa can adopt a viable but not culturable (VBNC) state, which renders it undetectable by current conventional food and water testing methods and makes it highly resistant to antibiotic treatment. Specific conditions can resuscitate these coccoid VBNC P. aeruginosa cells, which returns them to their active, virulent rod‐shaped form. Underreporting the VBNC cells of P. aeruginosa by standard culture‐based methods in water distribution systems may therefore pose serious risks to public health. As such, being able to accurately detect and quantify the presence of VBNC P. aeruginosa, especially in a hospital setting, is of critical importance. Herein, we describe a method to analyze VBNC P. aeruginosa using imaging flow cytometry. With this technique, we can accurately distinguish between active and VBNC forms. We also show here that association of VBNC P. aeruginosa with Acanthamoeba polyphaga results in resuscitation of P. aeruginosa to an active form within 2 h. Our approach could provide an alternative, reliable detection method of VBNC P. aeruginosa when coupled with species‐specific staining. Most importantly, our experiments demonstrate that the coculture with amoebae can lead to a resuscitation of P. aeruginosa of culturable morphology after only 2 h, indicating that VBNC P. aeruginosa could potentially resuscitate in piped water (healthcare) environments colonized with amoebae. © 2019 International Society for Advancement of Cytometry